Self-leveling concrete for laying floor heating pipelines in buildings and preparation method thereof
By using modified microcrystalline cellulose and polycarboxylic acid water reducer in concrete, the complex thermal decomposition and construction of the insulation layer in traditional floor heating systems is solved, and the high flowability, durability and strength of self-leveling concrete is achieved, which is suitable for laying of building floor heating pipelines.
Patent Information
- Application Number
- CN202410223557.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-02-29
AI Technical Summary
The polystyrene foam insulation layer used in traditional floor heating systems has problems such as thermal decomposition, insufficient compressive strength, complex and time-consuming construction, resulting in its failure in high-temperature environments, high maintenance costs and low construction efficiency.
Self-leveling concrete with modified microcrystalline cellulose and polycarboxylic acid water reducer is used to improve the flowability, durability and strength of the concrete through cross-linking reaction and esterification modification, forming a new type of concrete suitable for laying building floor heating pipelines.
The self-leveling characteristics of concrete are realized, the flowability and compressive strength are improved, the service life is extended, the maintenance and construction time is reduced, and the thermal insulation performance and construction convenience are good.
Smart Images

Figure BDA0004718868080000021 
Figure BDA0004718868080000061 
Figure FDA0005070007780000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building concrete, and relates to self-leveling concrete for laying building floor heating pipelines and a preparation method thereof. Background Art
[0002] Concrete refers to a mixture made of binder (organic, inorganic or organic-inorganic composite), granular aggregate, water, and chemical admixtures and mineral admixtures that need to be added in appropriate proportions, or a composite material with a stacking structure formed after hardening (usually cementitious materials, water, fine aggregate, coarse aggregate, admixtures and mineral admixtures are added when necessary, and are matched in appropriate proportions. It is the most widely used artificial civil construction material in the world. Concrete has the characteristics of abundant raw materials, low price and simple production process, so its usage is increasing. At the same time, concrete also has the characteristics of high compressive strength, good durability and a wide range of strength grades. These characteristics make its use very wide. It is not only used in various civil engineering projects, but also in shipbuilding, machinery industry, marine development, geothermal engineering, etc., concrete is also an important material.
[0003] Floor heating is the abbreviation of floor radiation heating. It uses the entire floor as a radiator, heats the floor evenly with a low-temperature heat medium not higher than 60°C, and supplies heat to the room through the floor by radiation and convection heat transfer to achieve the purpose of comfortable heating. The traditional floor heating structure includes a structural layer, a cement mortar leveling layer, an insulation layer, aluminum foil, geothermal pipes, plastic staples, a gravel concrete layer, and a floor decoration layer. The function of the floor heating insulation layer is to improve the insulation effect of the entire floor heating system and achieve a certain energy saving effect. It is located above the structural layer (original floor) and below the floor heating pipe, and is an indispensable part of the floor heating system. The insulation layer used in floor heating is mostly polystyrene foam, but polystyrene foam has a low heat resistance and begins to decompose at 74°C. When the temperature continues to rise, it will melt and shrink. The temperature of the floor heating hot water pipe is not constant, sometimes exceeding 74°C, which will cause the polystyrene foam to decompose and make the insulation fail, causing heat loss; the compressive strength of polystyrene foam is not enough, and it is easy to collapse when subjected to large or uneven force, resulting in high maintenance costs; using polystyrene foam as the insulation layer requires laying one by one, which is complicated, slow and labor-intensive. Secondly, laying one sheet at a time will produce many joints, which can easily cause cold bridges or hot bridges.
[0004] In recent years, concrete has gradually replaced polystyrene foam as floor heating insulation. Concrete does not have thermal decomposition, has a longer service life, has high compressive resistance, is safe to use, and has a fast construction speed. It can be poured and flattened, and has no joints, which reduces the heat loss caused by the joints.
[0005] "Application of Foam Concrete in Floor Heating Construction" (Cui Lijun, Shanghai Building Materials, 2019, Issue 2) discloses that floor heating foam concrete is a new type of high-quality foam concrete thermal insulation material and a new method for constructing floor heating insulation layers. Summary of the invention
[0006] The main purpose of the present invention is to provide a self-leveling concrete for laying floor heating pipelines in buildings and a preparation method thereof. The concrete prepared by the present invention has good fluidity, can be self-leveling, and has good durability and strength.
[0007] The present invention adopts the following technical solutions to achieve the above purpose:
[0008] A self-leveling concrete for laying floor heating pipelines in buildings, comprising the following components in parts by weight:
[0009]
[0010] Furthermore, the water reducing agent in the above concrete is a polycarboxylic acid high-efficiency water reducing agent.
[0011] The present invention provides a method for preparing the modified microcrystalline cellulose, comprising the following steps:
[0012] (1) adding malondialdehyde to microcrystalline cellulose after micronization to carry out a cross-linking reaction to obtain cross-linked microcrystalline cellulose;
[0013] (2) heating polyethylene glycol 6000 to a molten state under nitrogen protection, adding the cross-linked microcrystalline cellulose obtained in step (1), mixing evenly, cooling to room temperature, and obtaining a mixture for later use;
[0014] (3) adding water to dissolve the mixture obtained in step (2), ammonium persulfate and sodium bisulfite and heating to a gelatinized state, adding acrylic acid and dihydroxymethyl acrylate, reacting at a temperature of 120-150° C. for 2-3 hours, washing the reaction product with ethanol, and drying to obtain modified microcrystalline cellulose.
[0015] Furthermore, in the above-mentioned method for preparing esterified modified microcrystalline cellulose, the amount of malondialdehyde added in step (1) is 3-5% of the mass of the microcrystalline cellulose; the amount of polyethylene glycol 6000 added in step (2) is 20-30% of the mass of the microcrystalline cellulose; in step (3), the amount of ammonium persulfate added in step (3) is 3-5% of the mass of the microcrystalline cellulose, the amount of sodium bisulfite added in step (3) is 3-5% of the mass of the microcrystalline cellulose, the amount of acrylic acid added in step (40-60% of the mass of the microcrystalline cellulose, and the amount of dihydroxymethyl acrylate added in step (3) is 20-25% of the mass of the microcrystalline cellulose.
[0016] The present invention also provides a method for preparing the above concrete, comprising the following steps:
[0017] S1, mixing cement, slag powder, sand, gravel, expanded perlite and water uniformly to obtain cement slurry;
[0018] S2, adding silica sol, water reducing agent and modified microcrystalline cellulose to cement paste, stirring and mixing evenly, then adding polyoxypropylene glycerol ether, and continuing to stir until the mixture is evenly mixed to obtain concrete.
[0019] The present invention has the following beneficial effects:
[0020] 1. In the process of preparing the modified microcrystalline cellulose, acrylic acid, polyethylene glycol and dihydroxymethyl acrylate are used as grafting monomers, and ammonium persulfate and sodium bisulfite are used as initiators, which are grafted onto the microcrystalline cellulose skeleton, so that the modified microcrystalline cellulose has a more stable spatial structure and water retention and water absorption properties. Polyethylene glycol and dihydroxymethyl acrylate can form polyethylene glycol diacrylate under the reaction, and form a gelled form when used in concrete production, which can improve the working performance of the water reducer and change the fluidity of the concrete.
[0021] 2. The components of the present invention work synergistically to improve the fluidity and strength of concrete. The addition of water reducer can disperse and disintegrate the flocculated structure formed by cement at the initial stage of water addition, thereby releasing the water in the flocculated structure. The modified microcrystalline cellulose has high water absorption and water retention properties, and is organically combined with silica sol, which can achieve long-term and stable effective protection for concrete structures, improve the durability of concrete structures, extend their actual service life, and reduce later repairs and maintenance. At the same time, the addition of water reducer improves the workability of fresh concrete. Due to the significant decrease in the water-cement ratio in concrete, the pore volume inside the cement stone is significantly reduced. Silica sol has excellent permeability in fine cracks and fine sand, which can further fill the internal voids of the cement stone, making the cement stone more dense and significantly improving the compressive strength of the concrete.
[0022] 3. The concrete prepared by the present invention is self-leveling and has a compact structure. It can be applied to various floor surfaces, insulation layer backfilling, and building floor heating pipeline laying, and has a long service life. DETAILED DESCRIPTION
[0023] The present invention is further explained below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent modifications to the present invention by those skilled in the art all fall within the scope of protection of the claims of this application.
[0024] Example 1
[0025] Preparation method of modified microcrystalline cellulose:
[0026] (1) taking 20 kg of microcrystalline cellulose for micronization, adding 0.6 kg of malondialdehyde to the micronized microcrystalline cellulose for cross-linking reaction, and preparing cross-linked microcrystalline cellulose;
[0027] (2) Under nitrogen protection, 6 kg of polyethylene glycol 6000 was heated to a molten state, and then the cross-linked microcrystalline cellulose was added, mixed evenly, and cooled to room temperature to obtain a mixture for use;
[0028] (3) The above mixture, 1 kg of ammonium persulfate, and 1 kg of sodium bisulfite were dissolved in an appropriate amount of water and heated to a gelatinized state, 8 kg of acrylic acid and 5 kg of dihydroxymethylacrylate were added, and the mixture was reacted at 150° C. for 3 hours. The reaction product was washed with ethanol and dried to obtain modified microcrystalline cellulose.
[0029] Concrete preparation:
[0030] S1, 150kg of cement, 80kg of slag powder, 350kg of sand, 150kg of gravel, 30kg of expanded perlite and 180kg of water are mixed evenly to obtain cement slurry;
[0031] S2, add 3kg of silica sol, 5kg of polycarboxylic acid water reducing agent and 15kg of modified microcrystalline cellulose to the cement paste, stir and mix evenly, then add 1kg of polyoxypropylene glycerol ether, continue stirring until the mixture is evenly mixed, and obtain concrete.
[0032] Example 2
[0033] Preparation method of modified microcrystalline cellulose:
[0034] (1) taking 20 kg of microcrystalline cellulose for micronization, adding 1 kg of malondialdehyde to the micronized microcrystalline cellulose for cross-linking reaction, and preparing cross-linked microcrystalline cellulose;
[0035] (2) Under nitrogen protection, 4 kg of polyethylene glycol 6000 was heated to a molten state, and then the cross-linked microcrystalline cellulose was added, mixed evenly, and cooled to room temperature to obtain a mixture for use;
[0036] (3) The above mixture, 0.6 kg of ammonium persulfate, and 0.6 kg of sodium bisulfite were dissolved in an appropriate amount of water and heated to a gelatinized state, 12 kg of acrylic acid and 4 kg of dihydroxymethylacrylate were added, and the mixture was reacted at 150° C. for 2 hours. The reaction product was washed with ethanol and dried to obtain modified microcrystalline cellulose.
[0037] Concrete preparation:
[0038] S1, 120kg of cement, 100kg of slag powder, 300kg of sand, 200kg of gravel, 20kg of expanded perlite and 150kg of water are mixed evenly to obtain cement slurry;
[0039] S2, add 5 kg of silica sol, 2 kg of polycarboxylic acid water reducing agent, and 20 kg of modified microcrystalline cellulose to the cement paste, stir and mix evenly, then add 1.5 kg of polyoxypropylene glycerol ether, continue stirring until the mixture is evenly mixed, and obtain concrete.
[0040] Example 3
[0041] Preparation method of modified microcrystalline cellulose:
[0042] (1) taking 20 kg of microcrystalline cellulose for micronization, adding 0.8 kg of malondialdehyde to the micronized microcrystalline cellulose for cross-linking reaction, and preparing cross-linked microcrystalline cellulose;
[0043] (2) Under nitrogen protection, 5 kg of polyethylene glycol 6000 was heated to a molten state, and then the cross-linked microcrystalline cellulose was added, mixed evenly, and cooled to room temperature to obtain a mixture for use;
[0044] (3) The above mixture, 0.8 kg of ammonium persulfate and 0.8 kg of sodium bisulfite were dissolved in an appropriate amount of water and heated to a gelatinized state, 1 kg of acrylic acid and 5 kg of dihydroxymethylacrylate were added, and the mixture was reacted at 130° C. for 3 hours. The reaction product was washed with ethanol and dried to obtain modified microcrystalline cellulose.
[0045] Concrete preparation:
[0046] S1, 130kg of cement, 90kg of slag powder, 330kg of sand, 180kg of gravel, 25kg of expanded perlite and 160kg of water were mixed to obtain cement paste;
[0047] S2, add 4kg of silica sol, 3kg of polycarboxylic acid water reducing agent and 18kg of modified microcrystalline cellulose to the cement paste, stir and mix evenly, then add 1kg of polyoxypropylene glycerol ether, continue stirring until the mixture is evenly mixed, and obtain concrete.
[0048] Comparative Example 1
[0049] Preparation method of modified microcrystalline cellulose:
[0050] (1) taking 20 kg of microcrystalline cellulose for micronization, adding 0.8 kg of malondialdehyde to the micronized microcrystalline cellulose for cross-linking reaction, and preparing cross-linked microcrystalline cellulose;
[0051] (2) Add 100 kg of soybean oil ethanol solution (containing 20 kg of soybean oil) to the cross-linked microcrystalline cellulose obtained above, react at 120° C. for 3 hours, and dry the reaction product to obtain modified microcrystalline cellulose.
[0052] Concrete preparation:
[0053] S1, 130kg of cement, 90kg of slag powder, 330kg of sand, 180kg of gravel, 25kg of expanded perlite and 160kg of water were mixed to obtain cement paste;
[0054] S2, add 4 kg of silica sol, 3 kg of polycarboxylic acid water reducing agent and 18 kg of modified microcrystalline cellulose to the cement paste, stir and mix well to obtain concrete.
[0055] Comparative Example 2
[0056] Preparation method of modified microcrystalline cellulose:
[0057] (1) taking 20 kg of microcrystalline cellulose for micronization, adding 0.8 kg of malondialdehyde to the micronized microcrystalline cellulose for cross-linking reaction, and preparing cross-linked microcrystalline cellulose;
[0058] (2) Under nitrogen protection, 5 kg of polyethylene glycol 6000 was heated to a molten state, and then the cross-linked microcrystalline cellulose was added, mixed evenly, and cooled to room temperature to obtain a mixture for use;
[0059] (3) The above mixture, 0.8 kg of ammonium persulfate and 0.8 kg of sodium bisulfite were dissolved in an appropriate amount of water and heated to a gelatinized state, 1 kg of acrylic acid and 5 kg of dihydroxymethylacrylate were added, and the mixture was reacted at 130° C. for 3 hours. The reaction product was washed with ethanol and dried to obtain modified microcrystalline cellulose.
[0060] Concrete preparation:
[0061] S1, 130kg of cement, 90kg of slag powder, 330kg of sand, 180kg of gravel and 160kg of water are mixed evenly to obtain cement paste;
[0062] S2, add 3 kg of polycarboxylic acid water reducing agent and 18 kg of modified microcrystalline cellulose to the cement paste, stir and mix evenly, then add 1 kg of polyoxypropylene glycerol ether, continue stirring until the mixture is evenly mixed, and obtain concrete.
[0063] Comparative Example 3
[0064] S1, 130kg of cement, 90kg of slag powder, 330kg of sand, 180kg of gravel, 25kg of expanded perlite and 160kg of water were mixed to obtain cement paste;
[0065] S2, add 4kg of silica sol, 3kg of polycarboxylic acid water reducing agent and 18kg of modified microcrystalline cellulose to the cement paste, stir and mix evenly, then add 1kg of polyoxypropylene glycerol ether, continue stirring until the mixture is evenly mixed, and obtain concrete.
[0066] Performance Testing
[0067] 1. Thermal conductivity of concrete
[0068] The thermal conductivity of the concrete mortar prepared according to the methods described in the above Examples 1-3 and Comparative Examples 1-3 was tested. The test results are shown in Table 1.
[0069] Table 1 Thermal conductivity of concrete
[0070] mortar Thermal conductivity (Wm.K) Example 1 0.54 Example 2 0.63 Example 3 0.59 Comparative Example 1 0.66 Comparative Example 2 0.83 Comparative Example 3 0.75
[0071] From the results in Table 1, it can be seen that the thermal conductivity of the concrete prepared in the present application is significantly low, indicating that it has good thermal insulation performance. When used for floor heating laying, it can effectively avoid downward heat loss and achieve a good thermal insulation effect.
[0072] 2. Concrete fluidity and mechanical properties
[0073] According to the specifications of GB / T 50080 "Standard for Test Methods for Properties of Ordinary Concrete Mixtures" and GB / T 50010 "Code for Design of Concrete Structures", the concrete samples and products prepared according to the methods described in Examples 1-3 and Comparative Examples 1-3 were tested for fluidity and mechanical properties. The results are shown in Table 2.
[0074] Table 2 Concrete fluidity and mechanical properties
[0075]
[0076] From the results in Table 2, it can be seen that the concrete samples prepared by the present invention have good fluidity, and have good fluidity within 30 minutes, the time to pass through the V-funnel is short, and the compressive strength of the concrete products is also significantly higher, and all test data are better than the concrete samples and products obtained in the comparative example. The concrete mortar prepared by the present invention has good fluidity, is conducive to construction operation, can be self-leveling, and the fluidity is maintained for a long time, and has good durability and strength.
Claims
1. A self-leveling concrete for laying floor heating pipelines in buildings, characterized in that: In parts by weight, it contains the following components: The preparation method of the modified microcrystalline cellulose comprises the following steps: (1) adding malondialdehyde to microcrystalline cellulose for cross-linking reaction to obtain cross-linked microcrystalline cellulose; the amount of malondialdehyde added is 3-5% of the mass of the microcrystalline cellulose; (2) heating polyethylene glycol 6000 to a molten state under nitrogen protection, adding the cross-linked microcrystalline cellulose obtained in step (1), mixing evenly, cooling to room temperature, and obtaining a mixture for later use; the amount of polyethylene glycol 6000 added is 20-30% of the mass of the microcrystalline cellulose; (3) adding water to dissolve the mixture obtained in step (2), ammonium persulfate and sodium bisulfite and heating to a gelatinized state, adding acrylic acid and dihydroxymethyl acrylate, reacting at a temperature of 120-150° C. for 2-3 hours, washing the reaction product with ethanol, and drying to obtain modified microcrystalline cellulose; the amount of ammonium persulfate added is 3-5% of the mass of the microcrystalline cellulose, the amount of sodium bisulfite added is 3-5% of the mass of the microcrystalline cellulose, the amount of acrylic acid added is 40-60% of the mass of the microcrystalline cellulose, and the amount of dihydroxymethyl acrylate added is 20-25% of the mass of the microcrystalline cellulose.
2. The concrete according to claim 1, characterized in that The water reducing agent is a polycarboxylic acid high efficiency water reducing agent.
3. A method for preparing concrete as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1, mixing cement, slag powder, sand, gravel, expanded perlite and water uniformly to obtain cement slurry; S2, adding silica sol, water reducing agent and modified microcrystalline cellulose to cement paste, stirring and mixing evenly, then adding polyoxypropylene glycerol ether, and continuing to stir until the mixture is evenly mixed to obtain concrete.
Citation Information
Patent Citations
Self-compacting concrete, and preparation method and application thereof
CN109608124A
Modified concrete regenerated from waste freshly mixed concrete and preparation method of modified concrete
CN115073086A